Norepinephrine use in cardiogenic shock patients is associated with increased 30 day mortality - Xin Lu; Xue Wang; Yanxia Gao; Joseph Harold Walline; Shiyuan Yu; Zengzheng Ge; Mubing Qin; Huadong Zhu; Yi Li (ESC Heart Failure)
Abstract Aims Norepinephrine is recommended as a first‐line vasopressor agent in the haemodynamic stabilization of cardiogenic shock. The survival benefit of norepinephrine therapy has not been demonstrated in clinical practice, however. This study aimed to explore the relationship between norepinephrine use and outcomes in cardiogenic shock patients in real‐world conditions. Methods and results We conducted a retrospective cohort study based on the Medical Information Mart for Intensive Care III (MIMIC‐III) database. Cardiogenic shock patients were enrolled and categorized into a norepinephrine group or a non‐norepinephrine group. Propensity score matching (PSM) was used to control for confounders. Cox proportional‐hazards models and multivariable logistic regression were used to investigate the relationship between norepinephrine treatment and mortality. A total of 927 eligible patients were included: 552 patients in the norepinephrine group and 375 patients in the non‐norepinephrine group. After PSM, 222 cases from each group were matched using a 1:1 matching algorithm. Thirty day mortality for patients treated with norepinephrine was significantly higher than for those in the non‐norepinephrine group (41% vs. 30%, OR 1.61, 95% CI 1.09–2.39, P = 0.017; HR 1.50, 95% CI 1.09–2.06, P = 0.013). In the multivariable analysis, there was no significant difference between norepinephrine therapy and long‐term (90 day, 180 day, or 1 year) mortality (90 day (OR 1.19, 95% CI 0.82–1.74, P = 0.363), 180 day (OR 1.17, 95% CI 0.80–1.70, P = 0.418), 1 year (OR 1.14, 95% CI 0.79–1.66, P = 0.477). Patients in the norepinephrine group required more mechanical ventilation (84% vs. 67%, OR 2.67, 95% CI 1.70–4.25, P < 0.001) and experienced longer ICU stays (median 7 vs. 4 days, OR 7.92, 95% CI 1.40–44.83, P = 0.020) than non‐norepinephrine group. Conclusions Cardiogenic shock patients treated with norepinephrine were associated with significantly increased short‐term mortality, while no significant difference was found on long‐term survival rates. Future trials are needed to validate and explore this association.